EFEKTIFITAS PENGGUNAAN MEDIA AUGMENTED REALITY DALAM PEMBELAJARAN IPA KELAS VI TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR PADA MATERI SOLAR SYSTEM - Enik Wahyuningsih; Heri Maria Zulfiati; Daimul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the results of implementing the problem based learning (PBL) in terms of science lessons for 6th elementary school students. The research subjects were class 6th students at SD N 1 Sedayu, teachers and principals. The method used in this research is descriptive qualitative. Data analysis techniques include data collection, reduction, presentation and drawing conclusions as well as data collection techniques using observation, interviews and documentation. Science learning outcomes have increased from 58.7 before using the Media Augmented Reality to 82.7 after implementing Media Augmented Reality. Class completion increased from 45.8% to 83.3%. The results of interviews with students show that students feel happy in Media Augmented Reality learning. The results of interviews with teachers show that Media Augmented Reality can be a learning model to improve learning outcomes and student activity.